An Evaluation of the Effectiveness of Flextime Program as a Benefit in Improving Work–Life - Intan Intan; Muafi Muafi (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2026)
This study explores the perceived effectiveness of flextime in supporting work-life balance at PT Angkasa Pura Indonesia, Adisutjipto Airport Branch, Yogyakarta, focusing on how the policy is designed, experienced, and constrained in practice. This study used an exploratory qualitative descriptive design with an interpretivist orientation. Data were gathered through a semi-structured interview with a key informant, internal documentation, and field observations, and then analyzed thematically. Flextime supports work-life balance by reducing morning time pressure, providing time for non-work responsibilities, and signaling organizational trust. However, it is limited by the need for coordination, role differentiation, and airport operational requirements. Flextime should be viewed as a conditional resource, with its value depending on clear rules, managerial support, role fit, and alignment with operational needs. This study is a single-case analysis, limiting its generalizability, and relies on a small sample from one airport branch. This study contributes to the literature by showing how temporal flexibility works in high-discipline service environments and clarifying why its effectiveness is context-dependent.